Amniotic Membrane Transplantation in Surgically Induced Necrotizing Scleritis with Peripheral Ulcerative keratitis - Thatte, Shreya (Medknow Publications & Media Pvt Ltd, 2012)
A case of surgically induced necrotizing scleritis (SINS) after manual small incision cataract surgery that was associated with peripheral ulcerative keratitis (PUK) at a different site. Neither pathology responded to systemic steroids and progressed to become sight threatening, which is unusual. Progression of SINS was aggressive enough to cause a limbal wound gape, similarly PUK extended up to Descemet's membrane and emergency amniotic membrane transplantation (AMT) was required to save the globe. AMT may regress the scleral and corneal melting successfully. It is not common to observe SINS with PUK at a different site that is unresponsive to systemic steroids. AMT, though palliative treatment, was effective at treating this condition successfully.